2005
DOI: 10.1111/j.1365-3024.2005.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Intact glycans from cestode antigens are involved in innate activation of myeloid suppressor cells

Abstract: During helminthic infections, strong Th2 type-biased responses concomitant with impaired cell-proliferative responses to parasitic and unrelated antigens are major immunological hallmarks. Parasite glycan structures have been proposed to play a role in modulating these responses. To understand early events related to immune modulation during cestode infection, we have examined the role of intact glycans of antigens from Taenia crassiceps in the recruitment of innate cells. Soluble antigens from this cestode co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…Treatment with HdAg could ameliorate colitis via a variety of mechanisms (1,21,22). Antigens from the flatworms S. mansoni and Taenia crassiceps can mobilize myeloid-derived suppressor cells (MDSCs) (27,28). Assessing peritoneal cellularity, an obvious immune cell recruitment was noted 24 h after HdAg or LPS injection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with HdAg could ameliorate colitis via a variety of mechanisms (1,21,22). Antigens from the flatworms S. mansoni and Taenia crassiceps can mobilize myeloid-derived suppressor cells (MDSCs) (27,28). Assessing peritoneal cellularity, an obvious immune cell recruitment was noted 24 h after HdAg or LPS injection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In rats, MDSCs are characterized by coexpression of His48 and CD11bc (11). Expansion of MDSCs in the spleen and other peripheral organs has been found in cancers and some infectious diseases, such as toxoplasmosis (29), leishmaniasis (23), candidiasis (17), and helminthiasis (9,26). The role of MDSCs in PcP has not been investigated.…”
Section: Studies Of Various Inflammatory Components During Pneumocystmentioning
confidence: 99%
“…Moreover, a study by Terrazas and colleagues showed that inoculation of Ta. crassiceps glycans is sufficient to rapidly recruit MO-MDSC in a IL-4/IL-13-independent fashion, suggesting that this mechanism might be dominant in the acute infection phase [59]. Similarly, two schistosome oligosaccharides, lacto-N-fucopentaose III and lacto-N-neotetraose, triggered the rapid recruitment of suppressive CD11b …”
mentioning
confidence: 98%